Role of vaginal progesterone in reducing the rate of preterm labour in women with a sonographic short cervix - Mohapatra, Kirtirekha; Ghosh, Subhra; Dash, Rabinarayan; Sahoo, Balaram (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Preterm labour is responsible for not only neonatal morbidity and mortality but also has long term consequences .Till now there is no effective method of prevention. Progesterone has shown promising result. But ideal candidate, ideal route and when to start the treatment are still in dilemma. The present study was undertaken to know the role of progesterone on pregnant women with sonographically short cervix. Methods: This prospective case control study was started on 100 pregnant women with sonographic short cervix (≤2.5 cm) and between 19 – 29 weeks of gestation. 60 women, some with history of midtrimester abortion or preterm labour and some without this history were treated as cases and were given vaginal progesterone pessary 200 mg once daily till rupture of membrane or onset of labour or up to 36 weeks of gestation whichever is earlier. 40 women without any history of midtrimester abortion or preterm labour were treated as control and followed up. Results: Among the cases 18.3%, delivered preterm and 81.7% were term deliveries. Respective proportions among control were 40% and 60% respectively. 26 among the cases and all women of control group did not have history of preterm labour and mid trimester abortion. In the case group 26.9% and in the control group 40% had preterm deliveries. Though the proportion of labour was lower among the cases it is not statistically significant (p = 0.276). There is mean prolongation of gestational age by 8.4± 1.29 weeks in case group in present pregnancy compared the previous one in cases with history of preterm labour and midtrimester abortion which was statistically significant .When neonatal complication are compared there is no significant difference between the two groups. Conclusions: Vaginal progesterone started from midtrimester in pregnant ladies with short cervix with previous history of midtrimester abortion or preterm labour is effective in reducing the rate of preterm birth.